USE OF APPLICATION OF LETTER AGENDA MANAGEMENT INFORMATION SYSTEM (SIMAS) AT CENTER FOR UPPER LIVESTOCK BREEDING AND FORGIVE LIVESTOCK FEED BATURRADEN BANYUMAS REGENCY - Sartono Sartono; Teguh Teguh (DYNAMICS: Journal of Public Administration, 2022)
The purpose of this study was to describe the use of Management Information System Applications in the Management of Incoming and Outgoing Letters at the Baturraden Center for Superior Cattle Breeding and Forage. The data analysis technique used in this study is a descriptive qualitative approach with an interactive model using the "Purposive Sampling" technique. Aspects of Ease: Ability, Human Resources that can be relied on in working in accordance with existing provisions, readiness of Human Resources who can be relied on in completing tasks and have a level of loyalty in work. and admins have their own initiative in making good decisions, without having to depend on the leadership. (2) Efficiency Aspect: The use of storage space in the database is carried out to support the Agenda Letter Management Information System (SIMAS) which can be said to be good, employees also uphold archival rules in terms of security and maintenance. (3) Speed ​​Aspect: Utilization of the database allows to be able to store has been carried out properly in accordance with the direction of submission of Official Manuscripts.